Association Between Determinant Factors and Obesity Among Adolescents - Rizka Novitasary Hiola; Sunarto Kadir; Cecy Rahma Karim (GLOBAL HEALTH SCIENCE GROUP, 2025)
The prevalence of obesity has continued to increase every year. The WHO reports that in 2022, more than 160 million children and adolescents aged 5-19 years will be obese. Obesity has become a growing public health concern in low- and middle-income countries such as Indonesia due to changes in diet, sedentary lifestyles, and weak food control policies. This study aims to analyze the factors that contribute to obesity in adolescents, including genetic factors, gender, dietary Advanced Glycation End products intake (dAGE intake), eating frequency, water consumption, physical activity, and sleep duration. This study employed a quantitative approach with a cross-sectional design. The sample consisted of 50 students selected using a total population sampling technique. The research instruments included a 24-hour food recall, the International Physical Activity Questionnaire (IPAQ), and the Pittsburgh Sleep Quality Index (PSQI). All instruments demonstrated acceptable psychometric properties, with significance values below 0.05 and Cronbach’s alpha coefficients exceeding 0.70. Statistical analysis showed that physical activity (p = 0.027) and sleep duration (p = 0.006) were significantly associated with obesity. Other factors, including genetics, gender, dAGE intake, eating frequency, and water consumption, were not significantly associated with obesity. Sleep duration was identified as the most influential factor (Exp(B) = 0.103). Factors such as physical activity and sleep duration were associated with obesity. Adolescents need to focus on increasing physical activity, adopting healthy eating habits, and regulating optimal sleep duration as early obesity prevention measures.